Latihan Penguatan Kaki terhadap Keseimbangan Postural dan Kemampuan Fungsional Kaki pada Anak Usia 6-10 Tahun dengan Flexible Flatfoot - Zahra Sativani; Riza Pahlawi (Jurnal Ilmiah Kesehatan (JIKA), 2020)
The activities of children more involve the foot. One of the common problems in the foot is flexible flatfoot. A disturbance in the process of the formation of the arch foot could result in a deformation of the foot and increases the risk of an injury due to postural balance change. Normally, the arch of the foot formed the first five years for the age range of 2-6 years. The right choices of the intrinsic muscle exercises of the foot can prevent deformation and improve postural balance. This study aimed to discuss the effectiveness of foot strengthening exercise to improving postural balance and functional ability of foot on a flexible flatfoot 6-10 years old. This study was pre-experimental research with two groups of pre-post test design. The subjects of this research were 30 students that had been divided into two groups, case, and control. Each group consists of 15 students selected used purposive sampling method based on the criteria of inclusion that had been set. There was a significant difference after foot strengthening exercise between the case and control group, p-value = 0,000. The foot strengthening exercise could improve the postural balance and functional ability of the foot on a flexible flatfoot 6-10 years old.